Citizenship, co-ethnic populations and employment probabilities of immigrants in Sweden - Pieter Bevelander; Ravi Pendakur (Institute for the Study of Labor (IZA), 2009)
Over the last decades, Sweden has liberalized its citizenship policy by reducing the required number of years of residency to five for foreign citizens and only two for Nordic citizens. Dual citizenship has been allowed since 2001. During the same period, immigration patterns by country of birth changed substantially, with an increasing number of immigrants arriving from non-western countries. Furthermore, immigrants were settling in larger cities as opposed to smaller towns as was the case before. Interestingly, the employment integration of immigrants has declined gradually, and in 2006 the employment rate for foreign-born individuals is substantially lower compared to the native-born. The aim of this paper is to explore the link between citizenship and employment probabilities for immigrants in Sweden, controlling for a range of demographic, human capital, and municipal characteristics such as city and co-ethnic population size. The information we employ for this analysis consists of register data on the whole population of Sweden held by Statistics Sweden for the year 2006. The basic register, STATIV, includes demographic, socio-economic and immigrant specific information. In this paper we used instrumental variable regression to examine the clean impact of citizenship acquisition and the size of the co-immigrant population on the probability of being employed. In contrast to Scott (2008), we find that citizenship acquisition has a positive impact for a number of immigrant groups. This is particularly the case for non- EU/non-North American immigrants. In terms of intake class, refugees appear to experience substantial gains from citizenship acquisition (this is not, however, the case for immigrants entering as family class). We find that the impact of the co-immigrant population is particularly important for immigrants from Asia and Africa. These are also the countries that have the lowest employment rate.
urn:nbn:de:101:1-20091026150
Keywords: F22; J61; J68; 330; Immigration; naturalization; citizenship; ethnicity; Migranten; Staatsangehörigkeit; Wirkungsanalyse; Ethnische Gruppe; Berufliche Integration; Schweden